The Effect Of Calcium Hydroxide And Sugar Concentration On The Level Of Likeness Of Green Tomato (Solanum lycopersicum) Candied Fruit - Ananda Camelia; Hidayatun Muyasyaroh; Lucia Tri Pangesthi; Febriani Lukitasari (Jurnal Pendidikan Tata Boga dan Teknologi, 2026)
Output of green tomato has continued to rise, especially across East Java, yet this commodity is still rarely processed and tends to deteriorate quickly after harvest, leading to considerable postharvest waste. Because it carries substantial nutrient content and a relatively firm flesh, green tomato is well suited to be turned into a preserved product. This research was carried out to examine how varying concentrations of calcium hydroxide (slaked lime) and sugar influence the resulting characteristics and the degree of consumer acceptance of green tomato candy (Solanum lycopersicum). A factorial experimental design within a quantitative approach was applied, with the data evaluated through two-way ANOVA. Two levels of calcium hydroxide (0.3% and 0.5%) were combined with two levels of sugar (25% and 37.5%) as treatments. The variables assessed covered sensory attributes—color, aroma, flavor, texture, and overall liking—together with several chemical properties. Findings revealed that calcium hydroxide concentration had a marked influence on color, while sugar concentration and the interaction of both factors did not significantly alter aroma, flavor, texture, or overall liking. Panelists favored the formulation containing 0.3% calcium hydroxide and 37.5% sugar, which recorded a pH of 3.21, vitamin C content of 78.76 mg/100 g, total sugar of 39.51%, and calcium content of 11.48 mg/100 g. Overall, the study confirms that properly proportioned calcium hydroxide and sugar can enhance both the quality and the consumer acceptability of green tomato candy.